GERAKAN HIDUP BERSIH DAN SEHAT BEBAS SAMPAH DI DESA NAGRAK KEC. SUKARAJA KAB. BOGOR - Edison Hatoguan Manurung; Kasimir Sawito; Sri Prasetya Widodo; Abdul Mubarok; Dwi Purwanto; Sitti Wardiningsih (Indonesian Collaboration Journal of Community Services, 2022)
The application of clean and healthy living behaviors should be a daily habit. Although it seems simple, there are still many people who do not pay attention to the importance of clean and healthy living behaviors for healthy health, family, and the surrounding environment. Clean and healthy living behavior is a significant movement. Improve the quality of life and public health. Among the clean and healthy living behaviors is the habit of throwing garbage in its place and processing waste into useful items. The specific goal is 1) Improve understanding of healthy and waste-free living movements; 2) implement ways that can be done in carrying out healthy and waste-free lifestyle habits. Community Service activities that are carried out by the practitioners, according to the results of interviews with the Residents of Nagrak Kec. Sukaraja Kab. Bogor Village should be intensified again because many children and residents need assistance.i Most of the children of The Schooly of Children so that the model of community service carried out by students and lecturers of Universitasi Mpu Tantular Jakarta should also provide input and suggest that most of the Children of Anaki aged in school so that the model of community service carried out by students and lecturers of Universitasi Mpu Tantular Jakarta should also provide input and suggest that the Village Government also provide input and suggest that the Village Government also provide input and suggest that children of children aged in school so that the model of community service carried out by students and lecturers of Mpu Tantular University jakarta should also provide input and suggest that the Village Government also provide input and suggest that children from Children aged in school so that the model of community service carried out by students and lecturers of Universitasi Mpu Tantular Jakarta should also provide input and suggest that the Village Government also provide input and suggest that the school-aged Anaki di Anaki so that the model of community service carried out by students and lecturers of Universitasi Mpu Tantular Jakarta should also provide input and suggest that the Village Government also provide input and suggest that the school-aged Anaki model is carried out by students and lecturers of Mpu Tantular University jakarta should also provide input and suggest that the Village Government also provide input and suggest that the village government should also provide input and  providing intensive motivation to children and children also reminds with the implementation of healthy living patterns.i Activities of healthy living movements and waste-free that meet health requirements can also bring other benefits in the form of second-hand creations that can be sold so as to increase family income